Jason and the Golden Fleece - Apollonius (Clarendon Press, 1993)
This is a new translation of the only extant Greek epic poem to bridge the gap between Homer and late antiquity - a major product of the brilliant world of the Ptolemaic court at Alexandria, written by Apollonius of Rhodes in the third century BC In telling the dramatic story of Jason's quest for the Golden Fleece and his relations with the dangerous Colchian princess, Medea, Apollonius explores many of the fundamental aspects of life in a highly original way: love, deceit, heroism, man's ignorance of the divine, the limits of science. A major critical re-evaluation of the poem - one of Virgil's primary 'sources' for the Aeneid - is now under way among classicists and scholars in the field of comparative literature. This volume offers the first scholarly translation into English for many years, combining readability with accuracy and an attention to detail that will be helpful to readers both with and without Greek The explanatory notes and accompanying maps provide all necessary background information to enjoy the poem, while a comprehensive introductory essay sites the poem in its cultural and historical context
Aus dem Griech. übers.
Keywords: Greek poetry; Argonauts (Greek mythology); Epic poetry; Greek; Jason (Greek mythology); Medea (Greek mythology)